Gambaran berat badan akseptor KB suntik DMPA setelah empat kali suntikan - Yunaning Utami; Asmar Yetti Zein; Nanik Setiyawati (Jurnal Kesehatan Ibu dan Anak, 2014)
Injectable has a lot of side effects, such asmenstrual disorders, nausea, headaches, decreased sex drive (libido), chills, mastalgia (breast pain) and an increase in body weight. This study aims to describe the weight on injectable DMPA acceptors in Banguntapan health center II in 2010- in 2012. This research is a descriptive study cohort approach historical time. The population is all injectable DMPAacceptors who had completemedical records in health centers Banguntapan II beganin January 2010-December 31, 2012 a number of 86 acceptors. Average weight gain injectable DMPA acceptors at first injection was 48,8 kg, while the fourth injection is50,14 kg. More and more do DMPA injections, the average weight gain experienced by the higher. Most of the injectable DMPA acceptors weight gain is 83 people (96.5%after four injections), while the least weight loss is 1 person (1.2%). Changes in average bodyweight before and after usingDMPAinjections KBis 1.34 kg.